Impact of hydration on vocal loading using phonetogram measures - Ghosh, Sujan; Chatterjee, Indranil; Kundu, Piyali; Pani, Susmi; Kumar, Suman; Mandal, Joyanta Chandra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Vocal loading is a phenomenon that affects the vocal folds and voice parameters. Prolonged vocal loading may cause vocal fatigue. Hydration is one of the easiest precautions to reduce the effect of vocal loading. Voice range profile is an analysis of a participant’s vocal intensity and fundamental frequency ranges. Speech range profile is a graphical display of frequency intensity interactions occurring during functional speech activity. Phonetogram software can analyse VRP and SRP. Methods: Total sixty normophonic participants (thirty male and thirty female) were included in this study. Phonetogram, version 4.40 by Tiger DRS, software used to measure the voice range profile and speech range profile. For VRP, participants were asked to produce vowel /a/ and a passage reading task was given for SRP measurement. Results: All sample recording were done at pre vocal loading task, VLT and after hydration. Parameter that were used to measure the effects were Fo-range, semitone, max-F, min-F, SPL range, max-I, min-I, area (dB). Result showed that after VLT all other parameters like Fo-range, semitone, max-F, min-F, SPL range, max-I, min-I, area (dB) in VRP and SRP were reduced except min-F VRP in male, min-I VRP and min-I SRP in both male and female participants. After hydration all other parameters were improved except max-F VRP and min-F VRP in female, max-I VRP, min-F VRP and area VRP. Conclusions: This study concluded that vocal loading has negative impact on vocal fold tissue and mass.